The Influence of Organizational Culture, Islamic Work Ethic, and Exstrinsic Motivation on Nurse Performance - Tedy Firmansyah; Suyoto; Akhmad Darmawan; M. Agung Miftahuddin (Indonesian Journal of Business Analytics, 2025)
This study is about the influence of organizational culture, islamic work ethic, and extrinsic motivation affect the performance of nurses at RSU Muhammadiyah Siti Aminah Bumiayu. This study uses a quantitative approach with a sampling technique using purposive sampling with the criteria of permanent nurses who have a minimum work period of 1 year so that 128 respondents who meet the criteria. Data analyzed was performed using Structural Equation Modeling-Partial Least Square (SEM-PLS) to test the relationship between variables. The results of this study indicate that organizational culture and islamic work ethic have a positive and significant impact on nurse performance. However, extrinsic motivation has a negative and insignificant effect on nurse performance.